Postoperative cognitive changes after total knee arthroplasty under regional anesthesia. Issue 52 (December 2016) - Jeon, Young-Tae; Kim, Byung-Gun; Park, Young Ho; Sohn, Hye-Min; Kim, Jungeun; Kim, Seung Chan; An, Seong Soo; Kim, SangYun
Abstract: Background: The type of postoperative cognitive decline after surgery under spinal anesthesia is unknown. We investigated the type of postoperative cognitive decline after total knee arthroplasty (TKA). Neuropsychological testing was conducted and the changes in cerebrospinal fluid (CSF) biomarkers after surgery were evaluated. Methods: Fifteen patients who required bilateral TKA at a 1-week interval under spinal anesthesia were included. Neuropsychological tests were performed twice, once the day before the first operation and just before the second operation (usually 1 week after the first test) to determine cognitive decline. Validated neuropsychological tests were used to examine 4 types of cognitive decline: memory, frontal-executive, language-semantic, and others. Concentrations of CSF amyloid peptide, tau protein, and S100B were measured twice during spinal anesthesia at a 1-week interval. The patients showed poor performance in frontal-executive function (forward digit span, semantic fluency, letter-phonemic fluency, and Stroop color reading) at the second compared to the first neuropsychological assessment. Results: S100B concentration decreased significantly 1 week after the operation compared to the basal value (638 ± 178 vs 509 ± 167 pg/mL) ( P  = 0.019). Amyloid protein β1–42, total tau, and phosphorylated tau concentrations tended to decrease but the changes were not significant. Conclusion: Our results suggest that frontal-executive function declined 1 week after TKA under spinal anesthesia. The CSF biomarker analysis indicated that TKA under regional anesthesia might not cause neuronal damage.